Evaluation of gingival fiber retention technique on the treatment of patients with chronic periodontitis: A comparative study - Pooja Palwankar; Jagjit Dhaliwal; Vivek Mehta (Wolters Kluwer Medknow Publications, 2011)
The destructive action of the chronic periodontitis on the periodontal tissues has provided a continuous challenge to the dental profession to develop better methods to achieve repair of the recession regions and even regeneration of post periodontal tissues. Aims: To assess the effect of periodontal muco-periostal flap surgery with gingival fiber retention technique on minimizing the post surgical recession. Materials and Methods: The sample for the study comprised of 20 patients. The criteria for selection included patients with moderate periodontitis, with minimum recession in the anterior teeth, with adequate width of the attached gingiva, and with no traumatic occlusion. Periodontal muco-periosteal flap surgery with gingival fiber retention technique was done in the experimental site with internal bevel incision, and in control site, muco periosteal flap surgery with crevicular incision was done. Thereafter, observation period was of one week, four weeks, and eight weeks were done for both the sites. Statistical Analysis Used: The results were subjected to statistical analysis using student's t`-test. Results: The result of this study suggests that the periodontal flap surgery with gingival fiber retention technique has a beneficial effect on the anterior teeth, as it maintains the esthetics, recontours the gingiva with minimal recession. The area of recession was more on the control site as compared to experimental site at 4 weeks, 8 weeks and 12 weeks. Conclusions: Gingival fiber retention technique showed less post-surgical recession and also there was fall in values of plaque index, gingival index, and periodontal index scores, throughout the study.